Study on Preparation and Absorption of Alizarin Red from Mg/Al Layered Double Hydroxides. Issue 1 (March 2020) - Zhao, Wei; Chen, Youning; Li, Yuhong; Hu, Jiangshan; Deng, Yuling
Abstract: Mg/Al-LDH was prepared by co precipitation method at pH 10.5, 85 and hot water °C for 6 hours with controlling Mg/Al ratio (2:1 and 3:1) and mixing (at common stirring and ultrasonic stirring). The samples were characterized by the Fourier transform infrared spectro scopy and X-ray diffractometer analysis. Finally, the four group structure and excellent quality of hydrotalcite materials were obtained. Samples were calcined at 500 for 4h, and then °C the effects of different influencing factors on the adsorption of alizarin red by the adsorbent were studied. The results show that the prepared materials are layered with hydrotalcite and have good adsorption performance. When the pH value is 10, adding 1g of hydrotalcite and performing adsorption at low temperature, the adsorption rate reaches a maximum of 99%.